An error control coding in MAC layer for UWB WBAN - Khattiya, Wannarit; Timakul, Sekson; Choomchuay, Somsak (My University, 2013)
Nowadays, Wireless Body Area Network (WBAN) has become an interesting area of researchers since it can facilitate medical experts to provide a real-time health monitoring. The increasing of elder population is the main driven factor in implementing the medical intelligent services. Application of intelligent medical care system in the disaster environment is also not even less important. In such a vital application system as well as other large bandwidth requirement system, such as a cardiogram and heartbeat monitoring, the communication needs not only the reliability but also the realtime action. Considering the physical layer of IEEE 802.15.6 standard, Ultra Wideband offers an advantage in term of bandwidth availability. In this paper we propose the preliminary investigation of the application of error control code to MAC layer data. Of its both random and burst error correction capability, Reed-Solomon codes have been considered. In our investigation, several MIT-BIH Arrhythmia databases are chosen as input data. The coding scheme is applied to the 250 byte payload data. RS(250, k) which is the shorten version of RS(255, k) defined in GF(256) with variable code rate are investigated. AWGN channel and fading channels are employed to examine code's performance. © 2013 IEEE.
Keywords: Error correction control; UWB; Wireless body area network